Social marketing : an answer for cyberbullying in Singapore - Ang, Xue Ling (2012)
Cyberbullying, referring to the wilful, deliberate and repeated harm through the use of electronic devices such as computer, cell phones and other electronic devices, has increased in prevalence with the rising usage of the Internet and social media. Unfortunately, this social issue is not extensively studied in Singapore and hence this research study aims to obtain an in-depth and holistic picture of the cyberbullying scene in Singapore.